Fluoride Intake Through Dental Care Products: A Systematic Review - Saad, Hanan; Escoube, Raphaëlle; Babajko, Sylvie; Houari, Sophia (Frontiers in Oral Health, 2022)
Fluoride (F) is added to many dental care products as well as in drinking water to prevent dental decay. However, recent data associating exposure to F with some developmental defects with consequences in many organs raise concerns about its daily use for dental care. The aim of this systematic review is to evaluate the contribution of the dental care products in regards to overall F intake through drinking water and diet with measurements of F excretion in urine used as a suitable biomarker. According to PRISMA guidelines using key words related to chronic exposure to F in human population with measurements of F levels in body fluids, 1273 papers published between 1995 and 2021 were screened, and 28 papers were finally included for data extraction concerning daily F intake. The contribution of dental care products, essentially by toothbrushing with toothpastes containing F, was 38% in mean regardless of the F concentrations in drinking water. There was no correlation between F intake through toothpaste and age, nor with F levels in water ranging from 0.3 mg/L to 1.5 mg/L. There was no correlation between F intake and urinary F excretion levels despite an increase in its content in urine within hours following exposure to dental care products (toothpastes, varnishes or other dental care products). Consequences of exposure to F on health are discussed in the recent context of its suspected toxicity reported in the literature. Conclusions of the review aim to provide objective messages to patients and dental professionals worried about the use of F-containing materials or products to prevent initial caries or hypomineralized enamel lesions especially for young children.